Prognostic factors for patients with metastatic or recurrent thymic carcinoma receiving palliative-intent chemotherapy. (October 2020) - Okuma, Yusuke; Ko, Ryo; Shukuya, Takehito; Tateishi, Kazunari; Imai, Hisao; Iwasawa, Shunichiro; Miyauchi, Eisaku; Kojima, Tetsuya; Fujita, Yuka; Hino, Toshihiko; Yamanda, Shinsuke; Suzuki, Toshiro; et al.
Highlights: Metastatic involvements affected the survival of patients with thymic carcinoma. Hypoalbuminemia may affect to pharmacokinetic associated with poor survival. Controlling liver metastasis may improve prognosis of thymic carcinoma patients. Abstract: Background: Thymic malignancies are a model of rare cancer. However, little clinical data is available based on the large database. We aimed to clarify the prognostic factors, particularly the metastatic sites, for thymic malignancies using one of the largest, representative, multi-institutional databases, the NEJ023 database. Patients and Methods: Patients with Stage IVA/IVB or recurrent thymic carcinoma were enrolled between 1995 and 2014. Clinicopathologic information was evaluated, and the patients were subdivided according to the metastatic organs of involvement (serosal dissemination, liver, lymph node, pulmonary, and bone metastasis). A Kaplan-Meier analysis and multivariate Cox regression were used to evaluate survival. Results: Two hundred and seventy-nine patients with metastases and a predominantly squamous histology (66.7%) were included. Most patients (53.0%) had serosal dissemination, whereas 26.5%, 21.9%, 19.7%, and 15.8% had pulmonary, lymph node, bone and liver metastases, respectively. Over a median follow-up time of 21.5 months, the median overall survival (mOS) was 30.7 months. When the subjects were grouped according to involved metastatic sites, patients with more than 3 involved metastatic organs had the worst survival outcome. Among patients with isolated involvement, those with bone metastasis had the poorest survival, followed by patients with liver metastasis. Subjects with hypoalbuminemia also had poor survival outcomes. When patients treated with platinum and anthracycline-containing pharmacotherapy were compared with those treated with platinum and non-anthracycline-containing pharmacotherapy, no significant difference was observed. Bone metastasis ( P = 0.0005), liver metastasis ( P = 0.047), and hypoalbuminemia ( P = 0.0021) were identified as prognostic factors in a multivariate analysis. Conclusion: The site of metastatic involvement affects the survival outcomes of patients with thymic carcinoma, and this result may reflect the sensitivity of metastatic sites to pharmacotherapy. As a next step, controlling liver metastasis with pharmacotherapy could help to improve the prognosis of patients with thymic carcinoma.